Impacts of Different Rural Settlement Expansion Patterns on Eco-Environment and Implications in the Loess Hilly and Gully Region, China - Chen, Zongfeng; Li, Yurui; Liu, Zhengjia; Wang, Jieyong; Liu, Xueqi (Frontiers in Environmental Science, 2022)
While the eco-environmental effects of rural settlement expansion are of great significance to rural sustainable land use, the relationship between rural settlement expansion and eco-environment under different expansion patterns is still unclear. To fill this gap, the current study used Baota District of the loess hilly and gully region as a case study area. We first investigated the spatial-temporal expansion patterns of rural settlements from 1990 to 2015, and then estimated their impacts on ecosystem services by implementing the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model and the Global agro-ecological zones (GAEZ) model. Results showed that: (1) edge expansion was the primary pattern of rural settlement expansion in Baota District from 1990 to 2015, and the area of edge expansion was 757.40 hm2, accounting for 71.76% of the total expansion area of rural settlement. (2) Rural settlement expansion caused 1744.60 t loss of crop yield, 40,155.78 Mg C loss of carbon storage, and a significant decline in habitat quality of water area during 1990-2015. (3) According to the unit expansion area, the edge expansion and leapfrog expansion patterns contributed more to ecosystem services loss when compared to the infilling expansion pattern. (4) There were gradient differences in the impacts of three expansion patterns on ecosystem services, and the impacts were gradually weakened by increased distance. Accordingly, we concluded that the expansion of rural settlement reduced surrounding ecosystem services, especially food production service, and that the edge expansion and leapfrog expansion patterns had higher levels of stress on ecosystem services.